Seda: prototype expert system for the diagnosis of autoimmune diseases organ based internist - Cabrera Jojoa, Christian Humberto (Universidad y Salud, 2014)
Make a good diagnosis is vital to the successful in the treatment of a disease; therefore, tools that contribute to more accurate diagnosis are of great interest. Particularly immunology specialists do not have tools to support the organ-specific autoimmune diseases diagnosis process. This brings in this process specialists must resort to the formalized knowledge of this medicine area and their experience. But when the knowledge is not at hand or simply no one has the experience, the diagnosis of these diseases presents complications surely impact on patient health. From the IT field has been made different effors collaborate in diagnostic task; generally building Experts Systems that model the specialist knowledge to certain conditions. This paper proposes creation of an Expert System prototype for the Diagnostic of organ-specific Autoimmune diseases SEDEA, which integrates the clinical knowledge with the Internist descriptive model, through an ontology that allows handle the concepts using rules declared in the JESS inference engine, also offering interfaces for insert and process data easily.